THE DEVELOPMENT OF PRAYING ABILITY SCALE FOR MUSLIM WITH DIABETIC FOOT PROBLEM - Muhammad Jasfizal Jasni (Tesis, 2019)
In muslim patient who have diabetic foot problem, most of them having difficulty in doing prayer due to their variety diability. This newly developed scale is meant to gauge their ability to pray objectively.